Proteomic analysis detects deregulated reverse cholesterol transport in human subjects with ST-segment elevation myocardial infarction - Das, Apabrita Ayan; Choudhury, Kamalika Roy; Jagadeeshaprasad, M. G.; Kulkarni, Mahesh J.; Mondal, Prakash Chandra; Bandyopadhyay, Arun (Journal of Proteomics, 2020)
Reverse cholesterol transport (RCT) plays a critical role in removing cholesterol from the arterial wall. However, very few reports directly relate chronic inflammation and RCT with atherosclerosis. The present study was undertaken to investigate clinical implications of significantly altered circulating proteins in subjects with ST-segment elevation myocardial infarction (STEMI) in the manifestation of atherosclerotic events. Using a casecontrol design, more than 2500 proteins in both STEMI and healthy control subjects were identified by Orbitrap mass spectrometer. Quantitative proteomics study revealed downregulation of 26 proteins while expression of 38 proteins increased significantly in STEMI subjects compared to healthy controls. Pathway enrichment analyses indicated that most of the identified proteins were related to chronic inflammation, atherosclerosis, and RCT. Altered proteins such as AZGP1, ABCA5, Calicin, PGLYRP2, HAVCR2 and C17ORF57 were further validated by Western blotting analysis of human plasma. Pathophysiological significance was studied using macrophage derived foam cell for their critical role in RCT which indicated the imbalance of RCT via the interaction of AZGP1 with CD36. In summary, this study revealed a unique relationship of some novel proteins apparently responsible for impaired RCT and chronic inflammation leading to atherothrombosis and myocardial infarction. Significance: In the present study we identified >= 2500 unique circulating proteins in healthy control and clinically diagnosed STEMI subjects among which 423 proteins were found to be common in both the groups. We further show 64 proteins significantly different between healthy control and STEMI subjects. Proteomic analyses reveal a panel of proteins associated with atherosclerosis and STEMI. One of the proteins, AZGP1, an adipokine, is likely to act as the missing link between chronic inflammation and cholesterol transport. Deregulation of reverse cholesterol transport might be orchestrated by AZGP1, CD36, ABCA5, and PPARy in STEMI subjects. The present study employs shotgun and quantitative proteomics followed by in vitro validations demonstrating a biochemical basis for reverse cholesterol transport in the local milieu of the luminal wall of the artery which are critical for plaque build-up and atherosclerosis.
Keywords: Atherosclerosis; AZGP1; CD36; Plasma proteomics; Reverse cholesterol transport; STEMI